Catholic nuns and sisters in a secular age : Britain, 1945-90 - Mangion, Carmen M. (Book collections on Project MUSE., 2020)
"This book investigates the experiences of women religious in Britain from 1945 to 1990, identifying how communities and individual lives were influenced by both religious and secular social movements. Drawing on interviews with eighty women at nine different institutions, it examines youth culture, participatory democracy, the 'turn to self', post-war modernity, the voluntary sector and the women's movement. Though rooted in the experiences of women religious in Britain, it probes the transnational relationships and global interconnectivities between women religious across national divides, enriching our understanding of the interactions between religious bodies and society at large and shedding light on the evolving role of the Church in the twentieth century." -- Back cover.